Biodegradable polymeric insulin microneedles – a design and materials perspective review - Melbha Starlin Chellathurai; Syed Mahmood; Zarif Mohamed Sofian; Cheng Wan Hee; Ramkanth Sundarapandian; Haja Nazeer Ahamed; C. S. Kandasamy; Ayah R. Hilles; Najihah Mohd Hashim; Ashok Kumar Janakiraman (Drug Delivery)
Microneedle (MN) delivery devices are more accepted by people than regular traditional needle injections (e.g. vaccination) due to their simplicity and adaptability. Thus, patients of chronic diseases like diabetes look for alternative pain-free treatment regimens circumventing regular subcutaneous injections. Insulin microneedles (INS-MNs) are a thoughtfully researched topic (1) to overcome needle phobia in patients, (2) for controlled delivery of the peptide, (3) decreasing the frequency of drug administration, (4) to ease the drug administration procedure, and (5) thus increasing patient adherence to the treatment dosage regimes. MNs physically disrupt the hard outer skin layer to create minuscule pores for insulin (INS) to pass through the dermal capillaries into the systemic circulation. Biodegradable polymeric MNs are of greater significance for INS and vaccine delivery than silicon, metal, glass, or non-biodegradable polymeric MNs due to their ease of fabrication, mass production, cost-effectiveness, and bioerodability. In recent years, INS-MNs have been researched to deliver INS through the transdermal implants, buccal mucosa, stomach wall, intestinal mucosal layers, and colonic mucosa apart from the usual transdermal delivery. This review focuses on the design characteristics and the applications of biodegradable/dissolvable polymeric INS-MNs in transdermal, intra-oral, gastrointestinal (GI), and implantable delivery. The prospective approaches to formulate safe, controlled-release INS-MNs were highlighted. Biodegradable/dissolvable polymers, their significance, their impact on MN morphology, and INS release characteristics were outlined. The developments in biodegradable polymeric INS-MN technology were briefly discussed. Bio-erodible polymer selection, MN fabrication and evaluation factors, and other design aspects were elaborated.